A prairie perspective on global warming and climate change. (8th April 2009) - Griffin, Ronald
The Great Plains blankets eight states. It is dotted with oil patches, public utilities, farms, ranches, feed lots, meat-packing plants, medium size cities, military bases and tiny towns feeding on agricultural activity. The question is: what can leaders do for a desperate and aging population in a global warming environment to bring full employment to the region. This paper explores opportunities to capitalise upon environmentally friendly farming practices and agricultural waste to produce jobs, money, commercial opportunities, marketable sod, fertilisers, methane, electricity and securities (from the Chicago Climate Exchange) as answers for this question. The paper recounts the use of man made wetlands to sequester CO2; by-products from coal fired power plants; landfill methane; methane digesters and soil carbon projects to arrest heat and contribute to the campaign against global warming.